Efektivitas Kegiatan Pengabdian Masyarakat Dalam Mengembangkan Pembelajaran Agama Pada Anak Usia Dini Di Desa Sempa Jaya Kabupaten Karo - Hairani Ananda Putri; Insyafiatul Ummi; Afifah Afifah; Naena Suhailah; Rahma Adlya Zahra (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the impact of community service activities in developing religious education for early childhood in Sempa Jaya Village, Karo Regency. Developing religious education for early childhood in Sempa Jaya is an important step in building a strong spiritual and moral foundation for the younger generation. In this context, the approach focuses on interactive and enjoyable methods, such as evening Quranic reading, educational games, and creative activities like coloring and calligraphy. The research method employed is a qualitative descriptive approach, using data collection techniques such as interviews, participatory observations, and documentation. The results indicate that these activities have successfully enhanced children's understanding of religion, increased parental involvement, and fostered solidarity within the community. Children have shown significant progress in their ability to read the Quran and in moral values. In conclusion, these community service activities provide a positive contribution to children's religious education and require support from all stakeholders to address existing challenges.